The effect of electrical stimulation on the trunk control in young children with spastic diplegic cerebral palsy. - Park, E. S. (Korean Academy of Medical Sciences, 2001)
This study was designed to determine the effectiveness of electrical stimulation over the trunk in improving sitting balance in young children with spastic diplegic cerebral palsy who displayed poor trunk control. The subjects ranged in age from 8 to 16 months and were randomly assigned to two groups. Both group had physical therapy for 6 weeks. Electrical stimulation (ES) group had additional electrical stimulation over the abdomen and posterior back muscles. Radiographic studies were carried out on the whole spine while they were sitting before and after treatment. Kyphotic angle, Cobb's angle and lumbo-sacral angle were measured. Additionally, sitting score-Gross Motor Function Measure (GMFM) was also evaluated. There was no difference of these values at initial evaluation between the two groups. Following 6 weeks of intensive therapy, the changes of kyphotic angle and sitting score-GMFM were significantly higher in ES group statistically when compared with those of the control group. The Cobb's angle following treatment was improved in ES group, but not statistically compared with that of control group. This study suggests that electrical stimulation over the trunk become a beneficial therapeutic technique in improving the sitting posture and trunk control in young children with spastic diplegic cerebral palsy.